1073 What Happens To Patients After A Diagnosis Of Sleep Apnea?. (27th April 2018) - Bailes, S; Rizzo, D; Tran, D; Creti, L; Grad, R; Baltzan, M; Pavilanis, A; Fichten, C; Libman, E
Abstract: Introduction: Obstructive sleep apnea (OSA) common in older family medicine patients, yet hard to identify and even more challenging to treat. Little has been described about what happens to patients after a diagnosis is made and treatment is recommended. What determines which patients will adopt and persist with treatment? Methods: Consecutive older family medicine patients (n=35, M, age = 58) underwent in-laboratory polysomnography (PSG) and completed sleep-related questionnaires. Those receiving a diagnosis of OSA were followed for treatment according to usual medical practice. After two years, we enquired about what OSA treatment they had declined, initiated, maintained, or had given up. We examined their baseline responses to the Sleep Symptom Checklist (SSC) which assesses severity of sleep-related difficulty in four domains. Results: Thirty-one patients (13 men, 18 women) received a diagnosis of OSA. All were recommended treatment, including CPAP, dental appliance, surgery, nasal sprays, etc. Only 17 patients initiated treatment. Of the 13 who initiated CPAP treatment (2 men, 14 women), 10 (all women) were still using their machines at 2-year follow-up. Fourteen participants with OSA, 8 men and 6 women, refused treatment. Reasons given were: could not afford CPAP machine, did not want to sleep with a machine, did not believe in OSA. Group comparisons show that those who persisted with CPAP treatment showed more severe sleep-related symptoms at baseline than those who refused treatment, including worse daytime functioning (p<.01), sleep disorder symptoms (p<.006), and psychological adjustment (p<.01). There were no significant differences between these two groups in severity of insomnia symptoms or of OSA as measured by the AHI or SpO2. Conclusion: This older family medicine sample was not typical of a sleep clinic population since they were all offered sleep testing regardless of suspected OSA. The most notable results include 1) a high presence of OSA, 2). a high proportion of women volunteering for testing, and 3) that having more severe daytime, sleep disorder, and psychological symptoms may be an important motivation for adopting and persisting with CPAP therapy. Support (If Any): Canadian Institutes of Health Research.